2021
DOI: 10.3390/app11209410
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Characterization of Different Cutting Strategies for the Sintered ZnO Electroceramics

Abstract: Sintered zinc oxide (ZnO) ceramic is a fragile and difficult-to-cut material, so finishing operations demand handling cautious and accurate surface tolerances by polishing, grinding, or machining. The conventional machining methods based on grinding and lapping offer limited productivity and high scalability; therefore, their incapacity to prepare tight tolerances usually end up with uncontrolled edge chipping and rough surfaces in the final products. This study investigates microstructural features with surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It was also concluded that the main factor reducing ZnO ceramics machinability is excessive machining-induced damage like grain pull-out and edge chipping [31]. A study using a conventional milling strategy, based on the turning parameters, yielding the best results, showed that surface microstructure can have a noteworthy impact on the machining characteristics of this material and substantially better surface roughness was achieved by abrasive waterjet machining [32].…”
Section: Machining Strategymentioning
confidence: 99%
“…It was also concluded that the main factor reducing ZnO ceramics machinability is excessive machining-induced damage like grain pull-out and edge chipping [31]. A study using a conventional milling strategy, based on the turning parameters, yielding the best results, showed that surface microstructure can have a noteworthy impact on the machining characteristics of this material and substantially better surface roughness was achieved by abrasive waterjet machining [32].…”
Section: Machining Strategymentioning
confidence: 99%